Carijo: a cria dos festivais - Ribeiro, Jaqueline Alessandra Domanski (2013)
The objective of this research is a dissertation of the history of the idealization and a wide look into the festival's history of Carijo Da Canção Gaúcha that takes place in Palmeira das Missões, in northern of Rio Grande do Sul. This dissertation will be used along with theoretical foundation and empirical research, through interviews with people who are or have been part of the festival as well as the use of documents available that can serve as a historical source for this dissertation. The theoretical foundation is based on literature related to culture, gaucho culture, as well as anthropology and research methods. Although this the oretical view is necessary, the dissertation will work in empirical research, where "voices" tell the story, facts and important moments of the festival which is the state s patrimonial because the preservation of the gaucho music. Empirical research based on interviews and searching for information in documents such as protocol, newspapers, private collections and in the actual booklet of the festival. Was the affective reactions that made me choose the object to be analyzed, and therefore, may occur some moments of brilliance and interviews. We will cover a course of Festival: Silver Jubilee, counting from the first to the twenty-fifth edition. The study is grounded in established names when referring to Gaucha Culture as Ruben Oliven, Luiz Carlos Barbosa Lessa, João Paixão Côrtes, Sandra Pesavento, and other scholars who eventually opted to analyze other subjects of this culture and also concepts related to general culture, as Roque Laraia.